2019
DOI: 10.1021/acsomega.9b02589
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-Induced Expansion of Graphene Oxide Frameworks: Observation by in Situ Neutron Diffraction

Abstract: We have investigated adsorption-induced deformation in graphene oxide framework materials (GOFs) using neutron diffraction at sample pressures up to 140 bar. GOFs, made by the solvothermal reaction of graphite oxide and benzene-1,4-diboronic acid, are a suitable candidate for deformation studies due to their narrow (∼1 nm), monodispersed, slit-shaped pores whose width can be measured by diffraction techniques. We have observed, in situ, a monotonic expansion of the slit width with increasing pressure upon adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(57 citation statements)
references
References 58 publications
12
45
0
Order By: Relevance
“…60 The same principle as in XRD can be used for the study of GtO and GO using neutron diffraction as demonstrated by several studies. [116][117][118] Summarizing this section, the diffraction method is a powerful instrument for studies of GO swelling but it has also some limitations. For example, it provides only the estimation of the inter-layer distance based on averaging over many layers, typically hundreds or thousands.…”
Section: X-ray Diffraction Methodsmentioning
confidence: 99%
“…60 The same principle as in XRD can be used for the study of GtO and GO using neutron diffraction as demonstrated by several studies. [116][117][118] Summarizing this section, the diffraction method is a powerful instrument for studies of GO swelling but it has also some limitations. For example, it provides only the estimation of the inter-layer distance based on averaging over many layers, typically hundreds or thousands.…”
Section: X-ray Diffraction Methodsmentioning
confidence: 99%
“…In each simulation, the GOF structure (models i, ii, iv), GO, and DBA (model iii) were simulated fully atomistically, and the atoms were allowed to move with the exception of a fixed graphene bottom layer that simulates a solid graphite substrate, increases the stability of the simulation, and facilitates the analysis by keeping the structures roughly aligned parallel to the xy plane. This is a reasonable model since GOF samples have SSAs of ≈400 to 500 m 2 /g 18 compared to graphene’s theoretical surface area of 2600 m 2 /g.…”
Section: Methodsmentioning
confidence: 96%
“…In this paper, we focus on the structural properties of a type of GOF formed using an intercalation procedure originally proposed by Burress et al 9 and reproduced by Mercier et al 11 and Schaeperkoetter et al: 18 the dissolution of benzene-1,4-diboronic acid (DBA) in methanol and then intercalating the DBA into graphite oxide (GO), which lead to GOFs with SSA of ≈400 to 1000 m 2 /g and interlayer distances of ∼9 Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar relative comparison reported an increase of 37.5% and 17.3% in crystalline diameter for Coal EML and Coal SML, respectively. According to Schaeperkoetter et al (2019) this increase indicates successful incorporation of the gas molecules within the carbon crystals during the high-pressure adsorption process. The micrographs acquired from the FESEM of untreated and flue gas treated Coal EML and Coal SML are presented in Fig.…”
Section: Crystallinity and Morphology (Waxrd And Fesem-edx)mentioning
confidence: 99%